Zein regulating apatite mineralization, degradability, in vitro cells responses and in vivo osteogenesis of 3D-printed scaffold of n-MS/ZN/PCL ternary composite. Issue 34 (22nd May 2018) - Ru, Jiangying; Wei, Qiang; Yang, Lianqing; Qin, Jing; Tang, Liangchen; Wei, Jie; Guo, Lieping; Niu, Yunfei
Abstract : Zein regulating apatite mineralization, degradability, cells responses and osteogenesis of 3D-printed scaffold of n-MS/ZN/PCL ternary composite. Abstract : Bioactive and degradable scaffolds of nano magnesium silicate (n-MS)/zein (ZN)/poly(caprolactone) (PCL) ternary composites were prepared by 3D-printing method. The results showed that the 3D-printed scaffolds possessed controllable pore structure, and pore morphology, pore size, porosity and pore interconnectivity of the scaffolds can be efficiently adjusted. In addition, the apatite-mineralization ability of the scaffolds in simulated body fluids was obviously improved with the increase of ZN content, in which the scaffold with 20 w% ZN (C20) possessed excellent apatite-mineralization ability. Moreover, the degradability of the scaffolds was significantly enhanced with the increase of ZN content in the scaffolds. The degradation of ZN produced acidic products that could neutralize the alkaline products from the degradation of n-MS, which avoid the increase of pH value in degradable solution. Furthermore, the MC3T3-E1 cells responses ( e.g. proliferation and differentiation, etc. ) to the scaffolds were significantly promoted with the increase of ZN content. The in vivo osteogenesis of the scaffolds implanted the femur defects of rabbits was investigated by micro-CT and histological analysis. The results demonstrated that the new bone formation was significantly enhanced with the increase of ZN content, in which the C20 scaffold induced the highest new bone tissues, indicating excellent osteogenesis. The results suggested that the ZN in the ternary composite scaffolds played key roles in assisting bone regeneration in vivo .